QUALITY ASSESSMENT OF DISPOSED OILFIELD PRODUCED WATER IN THE NIGER DELTA - Kingsley Tamunokuro Amakiri; Naomi Amoni Ogolo (Romanian Journal of Petroleum & Gas Technology, 2023)
Oilfield produced water is the largest waste stream generated during oil and gas production and it has a high potential for contamination of marine environments when disposed without treatment. However, effective treatment before disposal is acceptable, but meeting the approved standards for discharge remains a challenge for the petroleum industry. To determine the extent of compliance with regulated standards in the Niger Delta, the physicochemical properties of produced water from two oil fields before and after treatment were investigated in this study. Concentrations of heavy metals and organic compounds in the water samples were analysed using atomic absorption spectrophotometer and gas chromatography respectively. Results show that oilfield waters from the Niger Delta contain high concentrations of heavy metals and organic compounds. It is observed that treated produced waters for disposal fall below the approved standards for heavy metals and organic compounds while concentrations of dissolved oxygen fall below 5mg/l which is detrimental to aquatic organisms. Disposal of large volumes of such waters into the ecosystem over an extended period of time endangers aquatic lives and degrades the marine environment. It is therefore recommended that produced water be re-injected back into the very formations from where they are produced to ensure environmental protection and preservation of marine ecosystems.